Superstar stats : everything cool about everyone who's hot! - Morse, Jenifer Corr (Gerogian Bay, 2008)
Hundreds of entries with biographical information and notable achievements of celebrities, directors, hip-hop and rock stars, supermodels, chefs, and the world's richest inventors and businesspeople.